Meningkatkan Pengetahuan Pencegahan Adiksi Gadget Menggunakan “Bogem Kaget” Melalui Pembelajaran Kegiatan Ekonomi Pada Siswa Kelas VII SMP Internat Alkausar Sukabumi - Bahar Sungkowo; Sandy Husein Abdullah; Ono Imron Rosyadi (Jurnal Penelitian Multidisiplin Ilmu, 2022)
The purpose of this classroom action research is to determine the increase in gadget anti- addiction knowledge through the delivery of economic activity learning on economic activity material, to know the activities of teachers and students, to find out the teacher's ability to manage the class and to know the extent to which students respond to the learning process in the knowledge of gadget anti- addiction. Research methods in the final report of this classroom action research is classroom action reseacrh method, namely classroom action research with the model of Kemmis and Taggar (1995). Data collection in classroom action research is using a written test in the form of a pretest, cycle reflection test, and absorption test. The data processing techniques are describe the data using quantitative - qualitative methods with data triangulation. The subjects of this study were students of class VII SMP Internat AlKausar with a total of 46 students. Time and duration of research held from March-November 2020, with the application of the classroom action research cycle as follows: 1. Cycle 1 Pre-PTK reflection, implementation of cycle I, and classroom action research 1hour reflection cycle I 1 hour. 2. Cycle 2, The results of action improvements in Cycle I, Implementation of Cycle II and classroom action research 1hour Reflection on cycle II 1 hour. Note: that Classroom Action Research is defined with only two cycles. Research results from the data obtained using the percentage method it can be concluded that there is a significant increase in knowledge which is 17.06 points. From an increase of 17.06 points, then conclusions can be confirmed classroom action research was successful and confirmed by criteria Pretty good. For percentage data from distributing questionnaires in this classroom action research, the results were obtained as follows: 1. There was a decrease in the threshold number from 80 to 85 which increased above the knowledge threshold by 17.06%. This indicates a significant development because 3 students scored above the 80-85 threshold and this has an impact to increase the percentage of students above the threshold 80-85. 2. The percentage results relate to student responses to the media bogem was shocked obtained proceedings as follows: most students / absolute feel the benefits the media bogem was shocked in increasing the knowledge of gadget anti-addiction by 94%, no one rated negative or 0%, and did not respond or abstrain in the questionnaire at 6%. So that the majority of students find it useful from the media bogem was shocked in increasing the knowledge of gadget anti-addiction.The results showed an increase in student learning outcomes each cycle individually with the percentage of pretest with those who got KKM scores and above KKM were 60.87%, Student scores in the first cycle that reaches the KKM and above the KKM is 95.65% and the value of the second cycle that gets the KKM score and above the KKM is 100%. VII SMP Internat AlKausar, Sukabumi Regency in the Very Good category. The media bogem was shocked at this responded positively by students due to several considerations namely: interesting and informative, the material can serve as advice to avoid gadget and internet addiction, and make them aware of balanced nutrition and getting enough rest.